Extra-corporeal membrane oxygenation for severe respiratory failure in the UK. (August 2020) - Czapran, Adam; Steel, Matthew; Barrett, Nicholas A
An overview of the current system for referrals and management of severe respiratory failure in the United Kingdom. We outline the history of severe respiratory failure centres, the process of retrieving a patient for veno-venous extra corporeal membrane oxygenation and highlight some common difficulties and pitfalls when referring these critically unwell patients